2016
DOI: 10.1111/jdi.12459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethanol extract of propolis on histopathological changes and anti‐oxidant defense of kidney in a rat model for type 1 diabetes mellitus

Abstract: Aims/IntroductionOxidative stress has a key role in the pathogenesis of diabetes. Propolis and its constituents have a wide range of medicinal properties against oxidative stress. In the present study, we evaluated the anti‐oxidant effects of ethanolic extracts of propolis on kidneys in diabetes mellitus rats.Materials and MethodsA total of 40 male Wistar rats were randomly divided into the following five groups: control, diabetes mellitus, diabetes mellitus with vehicle treatment, diabetes mellitus with propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 35 publications
5
61
0
Order By: Relevance
“…Propolis differs in composition due to differences in local vegetations, pharmacological activity of propolis is highly variable depending on its geographic origin [17,22]. In our study, reduced severity of dysplasia in cases, groups might be related to the presence of these active ingredients in propolis.…”
Section: Discussionmentioning
confidence: 61%
“…Propolis differs in composition due to differences in local vegetations, pharmacological activity of propolis is highly variable depending on its geographic origin [17,22]. In our study, reduced severity of dysplasia in cases, groups might be related to the presence of these active ingredients in propolis.…”
Section: Discussionmentioning
confidence: 61%
“…In this experimental study, the animals were randomly divided into six groups (n=8/each) as follows: 1) Control group (C) included 21-day pups without any intervention, 2) Sham group included 15-day pups that were beside their mothers during this period and received 0.1 ml saline solution daily, 3) Stress group (S), included 15-day pups that were separated from their mothers 6 hr/day during this period, 4) the S+P50 group which were under stress and received 50 mg/kg EIP daily, 5) the S+P100 group which were under stress and received 100 mg/kg EIP daily, and 6) S+P200 group which were under stress and received 200 mg/kg EIP daily ( 16 - 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our earlier studies have shown that the Iranian propolis extract could enhance the antioxidant levels and histopathological changes in the kidneys and control blood glucose and modulate some of the biochemical factors of diabetic rats, also prevent from increasing serum corticosterone and brain MDA levels and from decreasing ferric reducing antioxidant power (FRAP), superoxide dismutase (SOD) and glutathione peroxidase (GPx) levels in brain under prenatal stress ( 16 - 18 ). Propolis is one of the strongest natural antioxidants.…”
Section: Introductionmentioning
confidence: 99%
“…The extract was prepared according to a published method [12]. In summary, propolis was cut into small pieces (≈2-3 mm) and mixed with 99% ethanol, at a ratio of 1:10 (propolis:ethanol).…”
Section: Preparation Of Propolis Ethanolic Extract (Eep)mentioning
confidence: 99%